The poverty reduction support credit II project = (The World Bank in Vietnam (WB), 2003)
Vietnam's economy doubled in size during the last decade, while the rate of poverty was halved from 70 percent in the early 1990s to around 37 percent in 1998. Savings rates rose six-fold to around 25 percent of GDP. Exports grew by an average of 25 percent per year, transforming a food-deficit country into the second largest exporter of rice in the world. Social indicators improved markedly and across a broad front there was widespread and visible progress in the lives o f citizens. Vietnam navigated through the East Asian crisis thanks to prudent management o f it s economy, and took crucial steps to address the structural impediments to long- term growth and poverty reduction. The Second Poverty Reduction Support Credit builds on this performance, and the reinvigoration of the structural reform program, which was supported by the first Poverty Reduction Support Credit (PRSC 1) (report no. P7446) and the Poverty Reduction and Growth Facility (PRGF) of the International Monetary Fund (IMF). The Credit aims at sustaining the structural reforms, while extending into social and institutional areas, and is expected to help reduce the incidence of poverty further to 25 percent in 2004. The reform program supported through this process will be firmly aligned to Vietnam's blueprint for development, the Comprehensive Poverty Reduction and Growth Strategy (CPRGS). The three main pillars of the CPRGS are: (i) completing the transition to a market economy; (ii) making development inclusive; and (iii) building modern governance. In order to achieve these objectives, the continuing series of PRSCs, proposed by the Bank, would support measures to deepen the reforms taken under PRSC 1 and to extend sequentially the Bank's assistance to social and institutional areas. The current credit is the second in this series of operations, continuing the successful program started under PRSC 1. The credit will be disbursed upon declaration of effectiveness.